Religion in personality theory - Walborn, Frederick; ScienceDirect eBooks (Burlington : Elsevier Science, 2014)
Chapter 6 - Erik Erikson; RELIGIOUS BIOGRAPHY; ERIKSON AND RELIGION; THE PSYCHOSOCIAL STAGES AND RELIGION; MARTIN LUTHER; GANDHI'S TRUTH; EMPIRICAL EVIDENCE; SUMMARY; Chapter 7 - Eric Fromm; RELIGIOUS BIOGRAPHY; FROMM'S DEFINITION OF RELIGION; EXISTENTIALISM AND FREEDOM; THE EVOLUTION OF GOD; OLD TESTAMENT; NEW TESTAMENT; ZEN BUDDHISM; AUTHORITARIAN RELIGIONS; HUMANISTIC RELIGIONS; SUMMARY OF FROMM'S RELIGIOUS/SPIRITUAL WRITINGS; EMPIRICAL LITERATURE ON AUTHORITARIANISM; SUMMARY OF THE EMPIRICAL LITERATURE ON AUTHORITARIANISM; Chapter 8 - Burris Frederic Skinner; RELIGIOUS BIOGRAPHY.
Religion in Personality Theory makes clear the link between theory and research and personality and religion. Presently, most personality texts have a limited discussion of religion and reference few theorists other than Freud and Maslow in relation to the subject. This book reviews the theory and the empirical literature on the writings of 14 theorists. Every chapter concludes with a summation of the current research on the theorist's proposals. Identifies what major personality theorists say about religionInvestigates whether evidence supports or refute.
Chapter 15 -- John Bowlby.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Personality -- Religious aspects; FAMILY & RELATIONSHIPS -- Life Stages -- General; PSYCHOLOGY -- Developmental -- General; PSYCHOLOGY -- Developmental -- Lifespan Development; PSYCHOLOGY -- General; Personality -- Religious aspects; Electronic books